Assessment of quality of life and psychological state in patients with non-alcoholic fatty liver disease and overweight - Baka Олена; Skurat Катерина; Frankova Ірина; Potapov Олексій; Perehrestenko Олександр; Man’kovs’kyj Борис; Todurov Іван (Psychosomatic Medicine and General Practice, 2019)
Background. In recent years the most common liver disease in the world is a non-alcoholic fatty liver disease (NAFLD). Given that this disease is closely linked to metabolic disorders and, first of all, obesity, it significantly impairs the quality of life of patients, and may also be accompanied by depressive disorders. Mortality among patients with chronic liver disease (CKD) remains quite high, not only due to irreversible cirrhosis but also through numerous complications of the disease, such as HCC and related mental disorders, of which depression plays a special role Goal. To optimize treatment, analyze and identify optimal questionnaires for assessing the quality of life, screening and assessing the severity of depressive disorders in patients with CNS and obesity with varying degrees of severity of the disease. Materials and methods. The publications were analyzed in such bibliographic databases as Pubmed and Google Scholar for keywords: depression disorder, depression, quality of life, non-alcoholic fatty liver disease, obesity. Results. The main methods of assessing the quality of life (QOL) and depression in patients with NADH and obesity - questionnaires. During the analysis of the literature on the topic, it has been found that the most convenient clinical evaluation in the clinical practice is the Chronic Liver Disease Questionnaire (CLDQ) and the Liver Disease Symptom Index 2.0 (LDSI 2.0), and to assess the presence of symptoms of depression, the Beck Depression Inventory, BDI). Conclusions. The evaluation of NSC and the screening of depressive disorders in patients with NSCLC and obesity is very important for predicting the effectiveness of therapy, the choice of treatment tactics. Given that hronic Liver Disease Questionnaire (CLDQ) and the Liver Disease Symptom Index 2.0 (LDSI 2.0) have not been translated into Ukrainian, it is necessary to continue work towards the creation of the Ukrainian version, their adaptation and subsequent assessment of validity. Questionnaire that can be recommended for self-assessment of depression is the Beck Depression Scale. The use of questionnaires will help clinicians assess the psychological and physical condition of patients, and will allow them to choose the most effective tactics and management strategies for patients with NAFLD and obesity.